Validity Of Authentic Deeds Degraded In Court - Aulia, Nisa; Syuryani, Syuryani (Universitas Ibn Khaldun Bogor, 2024)
This research aims to determine the validity of authentic deeds that are degraded in court and to determine the legal consequences of authentic deeds that are degraded in court. Using a normative juridical approach, in the case it is discovered that the Plaintiff in this case wants the Deed made by the Notary to be legally invalid. The deed was canceled on the main reason that the signing of the deed was based on an unclear power of attorney and did not involve the plaintiff as the legal heir. The judge in his decision granted the plaintiff's lawsuit and canceled the deed. This cancellation means making a deed that was originally an authentic deed into a deed that is no longer authentic. There is a reduction (degradation) in the degree of the deed from the original authentic deed as stated in Article 1868 of the Civil Code to a private deed or becomes null and void in accordance with the provisions of Article 84 of the Law on the Position of Notaries. Cancellation of an authentic deed gives rise to new legal consequences in that the deed cannot be used as evidence in a civil case and does not give rise to legal consequences for the object or subject of the deed. legally, the deed is considered to have never existed.